2022
DOI: 10.1038/s41586-022-05091-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial retrons encode phage-defending tripartite toxin–antitoxin systems

Abstract: Retrons are genetic retroelements, commonly found in bacterial genomes and recently repurposed as genome editing tools. Their encoded reverse transcriptase (RT) produces a multi-copy single-stranded DNA (msDNA). Despite our understanding of their complex biosynthesis, the function of msDNAs and therefore, the physiological role of retrons has remained elusive. We establish that the retron-Sen2 in Salmonella Typhimurium encodes a toxin, which we have renamed as RcaT (Retron cold-anaerobic Toxin). RcaT is activa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 85 publications
2
66
2
Order By: Relevance
“…A common theme among retron-interacting proteins found in this and other studies, including T7 SSB, T5 A1, Rac prophage DNA exonuclease, E. coli DNA methylase (Bobonis et al, 2022) and RecBCD, is that they all have the capacity or predicted capacity to interact with DNA. It is possible that interaction of these proteins with the retrongenerated ssDNA forms part of the basis for their sensing by the retron system.…”
Section: Phage Triggers For Retron Defense Systemssupporting
confidence: 54%
See 4 more Smart Citations
“…A common theme among retron-interacting proteins found in this and other studies, including T7 SSB, T5 A1, Rac prophage DNA exonuclease, E. coli DNA methylase (Bobonis et al, 2022) and RecBCD, is that they all have the capacity or predicted capacity to interact with DNA. It is possible that interaction of these proteins with the retrongenerated ssDNA forms part of the basis for their sensing by the retron system.…”
Section: Phage Triggers For Retron Defense Systemssupporting
confidence: 54%
“…The retron RT reverse transcribes the non-coding RNA to form a chimeric RNA-DNA molecule which, together with the RT, has been hypothesized to sense phage infection. Defense by retrons involves cell suicide or growth arrest in response to phage infection (abortive infection), which is carried out by the associated effector protein (Bobonis et al, 2022; Millman et al, 2020). Based on phage escaper data, it was previously shown that retron Ec48 “guards” the cellular RecBCD complex, such that when phages inhibit RecBCD, the retron becomes active and leads the cell to growth arrest (Millman et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations